Pengaruh Kontrol Diri dan Lingkungan Toko Terhadap Perilaku Pembelian Impulsif Mahasiswa Penerima Beasiswa KIP-K Universitas Pendidikan Ganesha - Priska Happy Karina; M. Rudi Irwansyah (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2026)
This study aims to determine the effect of self-control and store environment on impulsive buying behavior of KIP-K scholarship recipients at Ganesha University of Education. This study uses a quantitative approach with a causal design. The research data were obtained by distributing questionnaires to 157 respondents who are KIP-K scholarship recipients using proportional stratified random sampling. The results of the study indicate that 1) self-control influences impulsive buying behavior, 2) store environment influences impulsive buying behavior, and 3) self-control and store environment simultaneously influence impulsive buying behavior. These findings indicate that the lower the self-control, the higher the tendency for impulsive buying, while an attractive store environment can encourage impulsive buying. Based on these results, it is recommended that KIP-K scholarship recipients be able to improve their self-control in managing their finances, and be wiser in dealing with various stimuli from the store environment so that the use of scholarship funds can be more optimal and on target.